Implementation and Operational Research: Integration of PMTCT and Antenatal Services Improves Combination Antiretroviral Therapy Uptake for HIV-Positive Pregnant Women in Southern Zambia. (1st December 2015) - Herlihy, Julie M.; Hamomba, Leoda; Bonawitz, Rachael; Goggin, Caitlin E.; Sambambi, Kennedy; Mwale, Jonas; Musonda, Victor; Musokatwane, Kebby; Hopkins, Kathryn L.; Semrau, Katherine; Hammond, Emily E.; Duncan, Julie; et al.
Abstract : Background: Early initiation of combination antiretroviral therapy (cART) for HIV-positive pregnant women can decrease vertical transmission to less than 5%. Programmatic barriers to early cART include decentralized care, disease-stage assessment delays, and loss to follow-up. Intervention: Our intervention had 3 components: integrated HIV and antenatal services in 1 location with 1 provider, laboratory courier to expedite CD4 counts, and community-based follow-up of women–infant pairs to improve prevention of mother-to-child transmission attendance. Preintervention HIV-positive pregnant women were referred to HIV clinics for disease-stage assessment and cART initiation for advanced disease (CD4 count <350 cells/μL or WHO stage >2). Methods: We used a quasi-experimental design with preintervention/postintervention evaluations at 6 government antenatal clinics (ANCs) in Southern Province, Zambia. Retrospective clinical data were collected from clinic registers during a 7-month baseline period. Postintervention data were collected from all antiretroviral therapy–naive, HIV-positive pregnant women and their infants presenting to ANC from December 2011 to June 2013. Results: Data from 510 baseline women–infant pairs were analyzed and 624 pregnant women were enrolled during the intervention period. The proportion of HIV-positive pregnant women receiving CD4 counts increased from 50.6% to 77.2% [relative risk (RR) = 1.81; 95% confidence interval (CI): 1.57 to 2.08; P < 0.01]. The proportion of cART-eligible pregnant women initiated on cART increased from 27.5% to 71.5% (RR = 2.25; 95% CI: 1.78 to 2.83; P < 0.01). The proportion of eligible HIV-exposed infants with documented 6-week HIV PCR test increased from 41.9% to 55.8% (RR = 1.33; 95% CI: 1.18 to 1.51; P < 0.01). Conclusions: Integration of HIV care into ANC and community-based support improved uptake of CD4 counts, proportion of cART-eligible women initiated on cART, and infants tested. Abstract : Supplemental Digital Content is Available in the Text.